A political study trip to the Netherlands to stimulate diffusion of Dutch bicycle policies in Sweden? - Strategier, Nina (2011)
Purpose: This thesis investigates if Swedish municipalities are interested to participate in a political study trip to the Netherlands with the goal to educate Swedish municipalities on Dutch bicycle policies. Furthermore it will explore what participants would expect during a political study trip. To educate Swedish municipalities there has to be a spread (diffusion) of Dutch bicycle innovations. Therefore the presence of the conditions for diffusion of innovation will be studied. Additionally, a political study trip to The Netherlands for Swedish municipalities will be developed. This study will be partly conducted for Cykelfrämjandet, an organisation that promotes cycling in Sweden. Methodologies: Next to theoretical research, a qualitative study has been carried out to meet the objectives of the research. Seven semi-structured face-to-face interviews with politicians and civil servants in four Swedish municipalities were conducted. Findings: In general, respondents are interested in a political study trip to the Netherlands. Moreover, they think it will be useful. Several elements that positively influence the process of diffusion are present. However, according to the respondents, it will be difficult for Swedish municipalities to actually implement new bicycle policies although they (possibly) would want to. The expectation of a study trip differs among the respondents. Further research is needed in order to explore if more Swedish municipalities would be interested in a study trip and if positive conditions for diffusion will lead to policy diffusion and maybe even the implementation of new policies. Implications: This study connects present literature with bicycle policies on the municipal level. Further it presents a model with elements that can influence the adoption of innovation. Finally it provides an advice for a three-day political study trip for Swedish municipalities to the Netherlands.